Towards a framework for spatial reasoning and primary mathematics learning: an analytical synthesis of intervention studies - Woolcott, Geoff; Le Tran, Thi; Mulligan, Joanne; Davis, Brent; Mitchelmore, Michael (Mathematics education research journal, 2022)
The connection between spatial reasoning and mathematics learning and pedagogy in primary school children has been the subject of an increasing number of studies in recent years. There has been no comprehensive analysis, however, of how studies based on spatial reasoning interventions may lead to improvements in students’ mathematics learning in school classroom environments. This article considers 18 studies selected from a combined systematic literature review of 133 studies, from Scopus and Education Research Complete (ERC) using PRISMA, and 23 studies recommended by the research team from bibliographies of major international research centres with a spatial reasoning dedication. This combination approach has allowed a synthesis of research and practice in an analytical way, assisting construction of a framework for spatial reasoning interventions for consideration in developing core knowledge and skills within the primary school mathematics curriculum. The findings highlight the importance of designing and evaluating spatial reasoning programs for primary school children in order to improve students’ mathematics classroom learning, including evidence from standardized tests, as they progress through the school system. The article supports the need for further research on interventions that provide sustainable school-based spatial reasoning programs.